What can you contribute the history of technology in the CTS education? - José Antonio Acevedo Díaz (Corporación Universitaria Minuto de Dios, 2010)
One of the many goals of technology education within CTS is to contribute to improving public understanding of the nature of technology. The article emphasizes the possibilities of the History of Technology in this area by clarifying and illustrating the articulation between society and technological innovations.